Bioprosthetic Valve Fracture to Facilitate Valve-in-Valve Transcatheter Aortic Valve Replacement. Issue 1 (2nd January 2021) - Sreedharan, Subhashaan; Sellers, Stephanie L.; Ihdayhid, Abdul Rahman; Landes, Uri; Blanke, Philipp; Allen, Keith B.; Chhatriwalla, Adnan K.; Pibarot, Philippe; Wood, David A.; Webb, John G.; Leipsic, Jonathon A.; Sathananthan, Janarthanan
ABSTRACT: Degeneration of surgical bioprosthetic heart valves (BPVs) occurs in up to one third of surviving patients within a decade of implantation and is a common cause of cardiovascular morbidity. Valve-in-valve transcatheter aortic valve replacement (VIV TAVR) is a safe and effective treatment for patients with failed BPVs who are unsuitable for reoperation. However, there may be patient-prosthesis mismatch (PPM) following VIV TAVR, particularly in patients with small BPVs. This may influence both morbidity and mortality. Bioprosthetic valve fracture (BVF) has emerged as a novel technique to prevent PPM. It involves high-pressure inflation of a non-compliant balloon to fracture the ring of the BPV, allowing for further expansion of the implanted transcatheter heart valve (THV) and thereby reducing residual transvalvular gradients. Early experience with this technique has been promising. This review will describe the procedural technique of BVF, explore the lessons learned from bench testing and early clinical experience, and discuss the limitations of the current literature as well as future directions. Abbreviations: ACn: ACURATE neo; BPV: Bioprosthetic heart valve; BVF: Bioprosthetic valve fracture; BVR: Bioprosthetic valve remodeling; EOA: Effective orifice area; NYHA: New York Heart Association; PPM: Patient-prosthesis mismatch; PWI: Pin-wheeling index; S3: Sapien 3; SAVR: Surgical aortic valve replacement; TAVR: Transcatheter aortic valve replacement; TPVR: Transcatheter pulmonary valve replacement; THV: Transcatheter heart valve; VIV: Valve-in-valve